SARS‑CoV-2 RBD219-N1C1: A yeast-expressed SARS-CoV-2 recombinant receptor-binding domain candidate vaccine stimulates virus neutralizing antibodies and T-cell immunity in mice. Issue 8 (3rd August 2021) - Pollet, Jeroen; Chen, Wen-Hsiang; Versteeg, Leroy; Keegan, Brian; Zhan, Bin; Wei, Junfei; Liu, Zhuyun; Lee, Jungsoon; Kundu, Rahki; Adhikari, Rakesh; Poveda, Cristina; Villar, Maria Jose; et al.
ABSTRACT: There is an urgent need for an accessible and low-cost COVID-19 vaccine suitable for low- and middle-income countries. Here, we report on the development of a SARS-CoV-2 receptor-binding domain (RBD) protein, expressed at high levels in yeast ( Pichia pastoris ), as a suitable vaccine candidate against COVID-19. After introducing two modifications into the wild-type RBD gene to reduce yeast-derived hyperglycosylation and improve stability during protein expression, we show that the recombinant protein, RBD219-N1C1, is equivalent to the wild-type RBD recombinant protein (RBD219-WT) in an in vitro ACE-2 binding assay. Immunogenicity studies of RBD219-N1C1 and RBD219-WT proteins formulated with Alhydrogel® were conducted in mice, and, after two doses, both the RBD219-WT and RBD219-N1C1 vaccines induced high levels of binding IgG antibodies. Using a SARS-CoV-2 pseudovirus, we further showed that sera obtained after a two-dose immunization schedule of the vaccines were sufficient to elicit strong neutralizing antibody titers in the 1:1, 000 to 1:10, 000 range, for both antigens tested. The vaccines induced IFN-γ IL-6, and IL-10 secretion, among other cytokines. Overall, these data suggest that the RBD219-N1C1 recombinant protein, produced in yeast, is suitable for further evaluation as a human COVID-19 vaccine, in particular, in an Alhydrogel® containing formulation and possibly in combination with other immunostimulants.